PERAN MODAL DALAM KEBERHASILAN USAHA KOPERASI TERATAI MANDIRI KELAPA DUA DEPOK - Zainal Arifin H. Masri; Fadillah Hisyam (Universitas Indraprasta PGRI, 2015)
The cooperative as a business entity or company needs capital to finance the business and cooperative organizations. Capital is a tool for to measure liquidity, activity and profitability of a company. Liquidity is the ability of the company to fulfill its financial obligations in the short term. Activities of the company is a measure of turnover, namely the length of time required in each rotation. The profitability of the company shows the company's ability to gain or profit. The aim of this study is to analyze the ratio of liquidity, activity and profitability of capital usage and analyze the influence of capital in business volume and SHU. The method used is descriptive analysis and simple regression analysis techniques. The descriptive analysis in the form of ratio analysis to determine liquidity, activity and profitability of capital utilization, while simple regression analysis is used to find the relationship between capital cooperative with the cooperative business volume and capital with SHU, as well as the volume of business with the SHU. The data required in this research is primary data and secondary data obtained from sources that required, that administrators, supervisors, managers and members of the Koperasi Teratai Mandiri Kelapa Dua, Depok. Data collection was done by interview, observation and documentation. Keywords : Capital, Liquidity, Activities, Profitability, Business Volume and SHU